(untitled) (African Journal of Law and Politics, 2023)
The publication by CONAC, the local anti-corruption squad, of its second report in 2013 is the basis for the reflections committed in this paper. Some highly placed personalities are alleged to have obtained land and land titles in the vicinity of the Kribi deep sea port. Their intentions were to fraud their way into obtaining compensation when eventually the land will be expropriated by the state for the port‟s infrastructure. The lands were obtained from local chiefs or individuals to whom they paid derisory sums in exchange. Given the personalities said to have alienated these lands, it can be assumed that the lands in question were “national lands”; a concept which became part of our land law since the 1974 land reforms. They consist on the one hand, of lands in the possession of families or individuals under customary law, and on the other hand, of communal or unoccupied lands generally placed under the authority of the chief-in council. While their alienation could be justified under customary law, the 1974 reforms changed the rules relating to the acquisition of title over these lands. This article reflects on the legality of the titles purported to have been acquired by the said personalities through an exploration of the notion of national lands and the technics of acquiring title over them.